A coordination scheduling mechanism to guarantee packet ordering in parallel packet switch. (1st December 2008) - Dai, Yi; Su, Jin-Shu; Zhang, Ying
A packet switch with parallel switching planes is a parallel packet switch (PPS). It is an open problem to design a PPS that is feasible to guarantee packet ordering with lower computation and communication overhead. Many solutions proposed previously are essentially impractical because of high communication complexity. In this paper, we attempt to make a PPS practical by using a simple cooperating scheduling mechanism between the round-robin demultiplexing at the inputs and the enhanced longest queue first (ELQF) scheduling at the central scheduler. In our scheme, no communication is needed during normal operation, and only sporadic communication between the central scheduler and demultiplexors is launched during the occurrence of starvation instead of each cell slot. As the experiment results demonstrate, our PPS offers improved delay performance compared with existing PPS designs.